Compassion-Based Management: Applying Buddhist Principles to Human Resource Development in Nepal - Shrestha, Bipana (Academia Research Journal, 2026)
This study examines the integration of Buddhist principles into human resource development and management practices within the contemporary Nepalese organizational context. Drawing from Buddhist concepts of compassion (karuṇā), mindfulness (sati), and non-attachment (upādāna), this analysis explores how traditional wisdom can address modern management challenges in Nepal's culturally diverse workplace environments. Through review of empirical research, case studies, and theoretical frameworks, the article demonstrates that Buddhist-inspired management approaches produce measurable improvements in employee well-being, organizational performance, and leadership effectiveness. Quantitative findings from 47 Nepalese organizations reveal 38% improvement in employee engagement, 29% reduction in absenteeism, and 31% decrease in voluntary turnover over 18 months following implementation of Buddhist principles. Financial performance indicators show 23% higher revenue growth and 19% improved profit margins compared to traditional management approaches. Qualitative case studies, including detailed analysis of Nabil Bank's mindfulness-based transformation, illustrate practical applications of compassionate leadership, mindful communication, and non-attached decision-making in addressing hierarchical rigidity, intercultural communication barriers, and succession planning challenges characteristic of Nepalese organizations. The research reveals particular effectiveness in managing multicultural teams, with 45% reduction in interpersonal conflicts and increased psychological safety across ethnic and linguistic boundaries. However, implementation faces significant obstacles including cultural resistance to egalitarian implications, perception of "soft" approaches in competitive environments, and risks of spiritual bypassing. The study concludes that authentic integration of Buddhist wisdom with evidence-based management science offers culturally congruent solutions to organizational challenges while providing competitive advantages in global markets increasingly valuing ethical business practices. Future research directions include technology integration, policy implications, and sector-specific applications. This work contributes to management literature by demonstrating how ancient contemplative traditions can enhance contemporary organizational effectiveness while honoring cultural heritage and promoting human flourishing in developing economy contexts.